Fashion and clothing design as a research topics: the case of articles published in the journal Educação Gráfica - Soares Junior, Glauber (2022)
This article was developed with the objective of identifying research whose themes include the areas of fashion and clothing design from the perspective of design, using the journal Educação Gráfica as an object of study. With regard to methodology, the research is classified as quantitative-qualitative in nature, of the descriptive type, being developed through a systematic analysis of the bibliography. Regarding the technical procedures, a content analysis was carried out through thematic networks, with the help of the IRaMuTeQ® software. As results, it is evident that of the total of 53 issues and 820 articles published over the 25 years of the journal’s existence, 49 papers cover various themes of fashion and clothing design, corresponding to 5.97% of the magazine’s scope. The articles found in the aforementioned themes were grouped and subdivided into 5 categories, namely: 1) research, teaching and methodology; 2) ergonomics and anthropometry; 3) communication and visual language; 4) design, technology and management; and 5) art, craft, design and contemporary fashion. It is important to note that articles with a theme related to surface design are distributed in different categories.